Laboratory fatigue models for recycled mixes with pozzolanic cement and bitumen emulsion - Kavussi, Amir; Nejad, Fereidoon Moghadas; Modarres, Amir (Journal of Civil Engineering and Management, 2011)
In recent years, due to technical and economical advantages, the production of pozzolanic cements have considerably extended. In the case of asphalt recycling, using Pozzolonic cements has several advantages. Lower initial stiffness and less shrinkage microcracks than Ordinary Portland Cement (OPC) are some benefits of pozzolanic cements which may reduce the probability of occuring premature cracking in recycled layer. In this reserach in order to investigate the effects of I (PM) pozzolanic cement on the fatigue cracking of recycled mixes with bitumen emulsion and develope fatigue models for these mixes, extensive indirect tensile fatigue and resilient modulus tests were performed at different temperatures and curing times. Test results showed that at high strain levels I (PM) cement specimens have superior fatigue behavior than OPC specimens. Furthermore, the effects of I (PM) cement on fatigue life of recycled mixes related to the initial strain level. Therefore a boundary strain level was determined. Above the boundary strain level, adding cement caused a reduction in fatigue life, whereas below that level the reverse was true. Finally based on laboratory testing results distinct models were established for different boundary strain levels.Pucolaninio cemento ir bituminių emulsijų mišinių perdirbimo laboratoriniai nuovargio modeliaiSantrauka. Pastaraisiais metais dėl techninių ir ekonominių veiksnių pucolaninio cemento gamyba gerokai padidėjo. Pucolaninio cemento naudojimas perdirbant asfaltą turi keletą pranašumų. Mažesnis pradinis standumas ir mažiau mikroįtrūkių nei įprastame portlandcementyje (Ordinary Portland Cement, OPC) – tai keletas pucolaninio cemento pranašumų, galinčių sumažinti priešlaikinio plyšių atsiradimo tikimybę perdirbamame sluoksnyje. Šiuo moksliniu tyrimu siekiama ištirti I (PM) pucolaninio cemento poveikį nuovargio plyšių atsiradimui perdirbamuose bituminių emulsijų mišiniuose ir sukurti šių mišinių nuovargio modelius. Buvo atlikti išplėstiniai netiesioginio tempimo nuovargio ir elastingumo modulių bandymai, esant skirtingoms temperatūroms ir džiūvimo laikui. Bandymų rezultatai parodė, kad esant aukštam įtempimo lygiui I(PM) cemento bandiniai yra atsparesni nuovargiui nei portlandcemenčio (Ordinary Portland Cement, OPC) bandiniai. Be to, perdirbtų mišinių iš I (PM) cemento tvarumas yra artimas pirminiam įtempimo lygiui. Todėl buvo nustatytas ribinis įtempimo lygis. Viršijus ribinį įtempimo lygį ir įmaišius cemento tvarumas sumažėja, o esant žemesniam įtempimo lygiui buvo gautas priešingas rezultatas. Galiausiai remiantis tyrimais buvo nustatyti atskiri modeliai skirtingiems ribiniams įtempimo lygiams.Reikšminiai žodžiai: šaltasis perdirbimas, bituminė emulsija, pucolaninis cementas, nuovargio modelis.